Effectiveness of Omalizumab in Severe Allergic Asthma: A Retrospective UK Real-World Study. (June 2013) - Barnes, Neil; Menzies-Gow, Andrew; Mansur, Adel H.; Spencer, David; Percival, Fran; Radwan, Amr; Niven, Rob
<x xml:space="preserve">Abstract</x> Objective. The aim of this study was to evaluate the "real world" effects of the monoclonal antibody omalizumab (OMB) when used to treat severe persistent allergic asthma in UK clinical practice. Methods. A 10-center retrospective observational study was carried out to compare oral corticosteroid (OCS) use and exacerbation frequency in 12 months pre- versus post-OMB initiation in 136 patients aged ≥12 years with severe persistent allergic asthma. All patients received ≥1 dose of OMB. Patients who had received OMB in a clinical trial were excluded. Data were obtained from hospital and if necessary general practitioners' (GPs') records on OCS use, lung function, hospital resource use, and routinely used quality of life (QoL) measures at baseline (pre-OMB), 16 weeks, and up to 12 months post-OMB initiation. Results. Mean total quantity of OCS prescribed per year decreased by 34% between the 12 months pre- and post-OMB initiation. During the 12 months post-OMB initiation, 87 patients (64%) stopped/reduced OCS use by 20% or more and 66 (49%) stopped OCS completely. Mean percent predicted forced expiratory volume in one second (FEV1) increased from 66.0% at baseline to 75.2% at week 16 of OMB therapy. The number of asthma exacerbations decreased by 53% during the 12 months post-initiation. Accident and emergency visits reduced by 70% and hospitalizations by 61% in the 12 months post-OMB initiation. Conclusion. This retrospective analysis showed a reduction in exacerbations and improved QoL as per previous studies with OMB. However, the total reduction in annual steroid burden and improved lung function in this severely ill group of patients taking regular or frequent OCS is greater than that seen in previous trials.